2010
DOI: 10.1271/bbb.100636
|View full text |Cite
|
Sign up to set email alerts
|

The Protein Encoded byNCgl1221inCorynebacterium glutamicumFunctions as a Mechanosensitive Channel

Abstract: The function of the NCgl1221-encoded protein of Corynebacterium glutamicum was analyzed using Bacillus subtilis as host because a method for preparing the giant provacuole required for electrophysiological studies has been established. Expression of NCgl1221 in a strain deficient in mscL and ykuT, both of which encode mechanosensitive channels, resulted in an 8.9-fold higher cell survival rate upon osmotic downshock than the control. Electrophysiological investigation showed that the giant provacuole prepared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
30
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 18 publications
1
30
0
Order By: Relevance
“…Electrophysiological analyses have indicated that NCgl1221 functions as a mechanosensitive channel. 19,20) Moreover, it was found that L-glutamate is indeed transported through this channel. 31) In the present study, we constructed a series of C-terminally truncated mutants of NCgl1221 to investigate the role of this C-terminal domain in glutamate secretion.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Electrophysiological analyses have indicated that NCgl1221 functions as a mechanosensitive channel. 19,20) Moreover, it was found that L-glutamate is indeed transported through this channel. 31) In the present study, we constructed a series of C-terminally truncated mutants of NCgl1221 to investigate the role of this C-terminal domain in glutamate secretion.…”
Section: Discussionmentioning
confidence: 98%
“…19) The mechanosensitive channel activity of NCgl1221 was also confirmed by patch-clump analysis using giant provacuoles of B. subtilis lacking mechanosensitive channels, MscL and YkuT (an MscS homolog). 20) These results suggest that NCgl1221 encodes a long-elusive L-glutamic acid exporter. Very recently, it was found that the NCgl1221 channel serves as a path for glutamate efflux.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…In addition, this is the first response of C. glutamicum to membrane tension alterations, which triggers all other metabolic adaptations leading to efficient glutamate production. The NCgl1221 (yggB) product has 4 transmembrane segments, is located in the cytoplasmic membrane [117] and has been recently shown to work as a mechanosensitive channel able to increase the cell survival rate of Bacillus subtilis after osmotic down-shock [118].…”
Section: Production Of L-glutamate By Corynebacterium Glutamicummentioning
confidence: 99%
“…59 SUPKULSUTRA et al surfactants or penicillin treatments (Nara et al, 1964;Takinami et al, 1965). It was recently shown that the NCgl1221 gene encoding a mechanosensitive channel is involved in the mechanism of L-glutamate secretion (Borngen et al, 2010;Hashimoto et al, 2010;Nakamura et al, 2007;Wachi, 2013). Specific mutations of NCgl1221 protein led to a constitutive L-glutamate secretion without any inducing treatments, while disruption of NCgl1221 greatly diminished L-glutamic acid secretion (Nakamura et al, 2007;Nakayama et al, 2012).…”
mentioning
confidence: 99%